Review of the Control System of the Tokiwa W500 Packing Machine at PT. Indofood CBP Sukses Makmur, Semarang Noodle Division - Ahmad Faidlon; Heru Saputro; Ariyanto Ariyanto; Boedi Lofian; Muhammad Nurul Latif; Syamsul Ma’arif (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2026)
The selection of this research topic is based on the important role of packing machines in the noodle production process. As consumer demand continues to increase and industrial competition becomes more intense, optimizing production efficiency is a critical requirement for manufacturing companies. This study focuses on the Tokiwa W500 Packing Machine used at PT. Indofood CBP Sukses Makmur, Noodle Division, Semarang. The research method involves a comprehensive review of the machine control system to evaluate its operational performance. Data collection was conducted through direct observation, structured interviews with machine operators, and relevant literature review. The review emphasizes system performance, operational efficiency, and the level of automation, while identifying potential areas for improvement. The results indicate that the Tokiwa W500 Packing Machine operates in a stable and consistent manner during the noodle packaging process. However, opportunities were identified to enhance the automation system in order to improve production efficiency and reduce the risk of human error. This study is expected to contribute to the development of more effective and optimized control systems for industrial packing machines.